Preliminary biological evaluation of 123I-labelled anti-CD30-LDM in CD30-positive lymphomas murine models. Issue 1 (1st January 2020) - Gong, Jianhua; Guo, Feihu; Cheng, Weihua; Fan, Hongqiang; Miao, Qingfang; Yang, Jigang
Abstract: Overexpression of CD30 has been reported on the surface of some T-cell lymphomas, especially on Hodgkin's lymphoma (HL) and anaplastic large cell lymphoma (ALCL). CD30 targeted immunotherapy has good clinical therapy response. We have produced a novel antibody drug conjugates (ADCs)-anti-CD30-LDM, which shows attractive tumour-targeting capability and extremely potent antitumor efficacy. To further investigate biological characteristics and promote clinical translation of anti-CD30-LDM, we constructed a radiolabeled 123 I-anti-CD30-LDM to evaluate the biodistribution characteristics. The anti-CD30-LDM was radioiodinated by the Iodogen method. The radiochemical purity of 123 I-anti-CD30-LDM was more over 98%, and the specific activity of 240.5 MBq/mg. The stability and the specificity of 123 I-anti-CD30-LDM were evaluated in vitro . Cellular binding assays were used to evaluate the binding capabilities in CD30-positive Karpas299 cells and CD30-negative Raji cells. B-NDG mice bearing Karpas 299 and Raji xenografts were used for in vivo biodistribution studies. Our results demonstrated that anti-CD30-LDM as an ideal ADC targeted to CD30, which was labelled easily with 123 I and obtained the sufficient yields. The 123 I-anti-CD30-LDM preserved specific binding to CD30 in vitro and uptake in tumour xenografts in B-NDG mice. These results are encouraging for anti-CD30-LDM as a promising clinical translational candidate for various CD30 positive lymphomas and other diseases.